1997
DOI: 10.1016/s0035-9203(97)90070-5
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C antibody prevalence in blood donors in different governorates in Egypt

Abstract: Markers of hepatitis B virus (HBV) and hepatitis C virus (HCV) infections were sought in serum samples from 2644 blood donors in 24 of Egypt's 26 governorates. Of the 2644 samples, 656 (24.8%) were shown to contain anti-HCV immunoglobulin G antibody by Abbott second generation enzyme immunoassays (EIA). Of 85 EIA-positive samples tested by recombinant immunoblot assay, 72 (85%) were positive. HCV seroprevalence in the governorates ranged from zero to 38%; 15 governorates (62%) had an HCV antibody prevalence gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
76
1
3

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(85 citation statements)
references
References 15 publications
5
76
1
3
Order By: Relevance
“…These data are concordant with the findings of other community-based studies in the Nile delta that have indicated that this region of Egypt has among the highest levels of seroprevalence of HCV in the world. [1][2][3][4]17,18 Indeed, if as seems plausible, 17,18 the high seroprevalence of HCV is relatively uniformly distributed throughout the Nile delta, the 40% seroprevalence of HCV among persons aged ten years and over in Kalama would translate into approximately eight million HCV-infected Nile delta residents in this age group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data are concordant with the findings of other community-based studies in the Nile delta that have indicated that this region of Egypt has among the highest levels of seroprevalence of HCV in the world. [1][2][3][4]17,18 Indeed, if as seems plausible, 17,18 the high seroprevalence of HCV is relatively uniformly distributed throughout the Nile delta, the 40% seroprevalence of HCV among persons aged ten years and over in Kalama would translate into approximately eight million HCV-infected Nile delta residents in this age group.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22] However, despite recognition of the extremely high seroprevalence of HCV in the Nile delta and the Nile river valley south of Cairo, 17 little is known about the relationship between HCV and cirrhosis in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…14,19,22 Now that HCV has become highly prevalent in Egypt, its spread apparently continues via poorly understood parenteral routes, as suggested by Quinty and others. 42 Although blood banks in Egypt started to screen for HCV in 1993, 13 blood transfusion is still a major risk factor for acquiring HCV infection, since blood donated for transfusion is commonly supplied by relatives of patients rather than blood banks. Surgical treatment with contaminated equipment may represent another major risk factor, because all hospitals may not disinfect their equipment properly.…”
Section: Discussionmentioning
confidence: 99%
“…12 Other groups thereafter found HCV seroprevalence rates ranging from 6% to 38% with an average of approximately 15%. [12][13][14][15][16] The reasons behind these high HCV infection rates being 5-35-fold higher than reported elsewhere in the world are still unknown. In Egypt, the HCV seroprevalence was 55% among children who had received blood transfusions and 67% among patients receiving renal dialysis, whereas the HCV seroprevalence was 10% among sexually transmitted disease patients and even lower among children who had never received blood transfusions.…”
mentioning
confidence: 99%
“…HCV infection is more common among adults, males, those with a history of schistosomiasis, and those living in rural communities of Lower Egypt. 8,12,14 However, the epidemiologic and biologic basis for HCV transmission in Egypt is not known. A community cohort was established in a rural, schistosomiasis-endemic area of the Lower Nile Delta to further study HCV infection in rural Egypt.…”
mentioning
confidence: 99%